MENGGALI PENGARUH PEMAHAMAN PERPAJAKAN TERHADAP MINAT KARIER MAHASISWA AKUNTANSI: STUDI KASUS DI UNIVERSITAS LOGISTIK DAN BISNIS INTERNASIONAL - Riani Tanjung; Cendy Febrinanto (JAMER : Jurnal Akuntansi Merdeka, 2024)
Tax knowledge plays an important role in shaping the career interests of accounting students in pursuing a career in the field of taxation. This study aims to evaluate the extent to which tax knowledge influences the career interests of accounting students at the International Logistics and Business University in choosing a career in taxation. The research method used is quantitative with an associative approach, utilizing primary data. The analysis techniques used include validity tests, reliability tests, correlation coefficient tests, simple regression analysis, determination coefficient tests, and t-tests. The results of the study indicate that tax knowledge significantly influences students' interest in pursuing a career in taxation. The validity test shows valid results, while the reliability test confirms that the data used is reliable. The correlation test results demonstrate a strong relationship between tax knowledge (variable X) and career interest (variable Y). The simple regression analysis shows that variable X has a positive impact on variable Y, with a determination coefficient of 49.4%. This means that nearly half of the students' interest in pursuing a career in taxation is influenced by their knowledge of taxation, while the remaining portion is influenced by other factors. The t-test reveals a significance value of less than 0.05, indicating that there is a significant influence between tax knowledge and the career interest of accounting students in the field of taxation.